Efektivitas Instagram sebagai Media Promosi dalam Menarik Minat Pengunjung di Kopi Sadis Medan - Rizki Amalia (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2022)
This article aims to find out the effectiveness of Instagram as a promotional medium in attracting visitors in coffee shop “Kopi Sadis”. Social media is currently the choice of many people as a means of promotion and marketing. One of the social media that some people use in promoting online businesses is Instagram. Instagram is an online media that makes it easier for its users in various ways, including marketing products and services. Kopi Sadis is one of the online businesses that utilizes Instagram media in marketing the products they sell. Starting from the types of drinks, food, to the atmosphere of the café they post on Instagram. This article uses descriptive qualitative research methods. The source of the data was obtained from interviews with the owner of Kopi Sadis, admin and also visitors of Kopi Sadis. The results showed that Instagram is very effective in attracting the interest of Kopi Sadis visitors in Medan. The interest in sadistic coffee has increased since it was first introduced through Instagram media.